2022
DOI: 10.1111/nph.18055
|View full text |Cite
|
Sign up to set email alerts
|

Identification of conserved and new miRNAs that affect nodulation and strain selectivity in the Phaseolus vulgaris–Rhizobium etli symbiosis through differential analysis of host small RNAs

Abstract: Phaseolus vulgaris plants from the Mesoamerican centre of genetic diversification establish a preferential and more efficient root nodule symbiosis with sympatric Rhizobium etli strains. This is mediated by changes in host gene expression, which might occur either at the transcriptional or at the post-transcriptional level. However, the implication of small RNA (sRNA)mediated control of gene expression in strain selectivity has remained elusive.sRNA sequencing was used to identify host microRNAs (miRNAs) diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 98 publications
(157 reference statements)
0
3
0
4
Order By: Relevance
“…Usually, plant miRNAs associate with Argonaute protein 1 to promote RNA posttranscriptional gene silencing by coupling target sequences and determining RNA slicing and/or translation inhibition [ 35 , 36 ]. In the last few years, many miRNAs have been identified in P. vulgaris [ 37 , 38 ]. Based on this second hypothesis, the α-glucosidase inhibitory activity observed in the cultivars without α-AI activity could be linked to the presence of flavonol glycosides and caffeic acid derivatives in the homogenates.…”
Section: Resultsmentioning
confidence: 99%
“…Usually, plant miRNAs associate with Argonaute protein 1 to promote RNA posttranscriptional gene silencing by coupling target sequences and determining RNA slicing and/or translation inhibition [ 35 , 36 ]. In the last few years, many miRNAs have been identified in P. vulgaris [ 37 , 38 ]. Based on this second hypothesis, the α-glucosidase inhibitory activity observed in the cultivars without α-AI activity could be linked to the presence of flavonol glycosides and caffeic acid derivatives in the homogenates.…”
Section: Resultsmentioning
confidence: 99%
“…The miR390 guides ARGONAUTE 7 (AGO7)‐mediated endonucleolytic cleavage of the TAS3 transcript, triggering the production of secondary trans ‐acting small interference RNAs (tasiRNAs), which bound to AGO1 guide endonucleolytic cleavage of ARF2 , ARF3 and ARF4 mRNAs (Xia et al ., 2017). We have previously shown that the miR390/ TAS3 / ARF module mediates the control of lateral root formation and root nodule symbiosis (Hobecker et al ., 2017; Kirolinko et al ., 2021; Castaingts et al ., 2022). Activation of the miR390/ TAS3 / ARF module by overexpression of miR390 in M. truncatula roots altered root architecture and impaired nodule formation and infection by Sinorhizobium meliloti , whereas inactivation of this module by expression of a target mimicry of miR390 or mutations in AGO7 promotes nodule organogenesis and bacterial infection (Hobecker et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Estudios transcriptómicos nos han permitido identificar transcriptos que se acumulan diferencialmente en respuesta a cepas de rizobio que son seleccionados por la planta y que presentan una mayor eficiencia simbiótica. A partir de esta información se identificaron RNAs no codificantes pequeños (miRNAs y siRNAs) (Castaingts., 2022), RNAs no codificantes largos (lncRNAs) y mRNAs que codifican proteínas que participan del silenciamiento postranscripcional (Dalla Via et al, 2015;Clúa et al, 2022).…”
Section: Hipótesis De Trabajo Y Objetivo Generalunclassified
“…Teniendo en cuenta que la proteína IDN2 de A. thaliana participa en el proceso de metilación del DNA guiada por RNA y que plantas mutantes idn2 de Arabidopsis exhiben niveles de metilación de citosinas alterados en todos sus contextos (CG, CHG y CHH) (Ausin et al, 2009), nos propusimos identificar cambios en los niveles de metilación del DNA como consecuencia del silenciamiento de PvIDN2 en P. vulgaris en el contexto de la infección rizobiana. A partir de bibliotecas generadas en nuestro laboratorio de RNAs pequeños (sRNAs) de plantas de poroto de la variedad Mesoamericana NAG12 24 hpi con la bacteria más eficiente R. etli SC15, con la bacteria menos eficiente 55N1 o con medio YEM como control (Castaingts et al, 2022), se llevó a cabo un análisis bioinformático para identificar pequeños RNAs de interferencia (siRNAs) de 24 nucleótidos que actúan a nivel de la cromatina promoviendo su compactación (denominados hetsiRNAs, por siRNAs de heterocromatina) (resultados no publicados, Artunián, Reynoso, Blanco). Se identificaron 236 picos de hetsiRNAs diferencialmente acumulados, de los cuales 25 están próximos a genes regulados en respuesta a la cepa nodC-α (SC15) o nodC-δ (55N1).…”
Section: Caracterización De Los Cambios En El Estado De La Metilación...unclassified